Seroprevalences of Babesiea species in Cattle in Elazi?, Malatya and Tunceli provinces - Aktaş, Münir; Dumanli, Nazir; Karaer, Zafer; Çakmak, Ayşe; Sevgili, Murat (My University, 2001)
This study was carried out in cattle in Elazi?, Malatya and Tunceli provinces between May 1997 and March 1998 to determine the seroprevalence of Babesia species. Serum samples were collected from a total of 741 cattle in Elazi?, Malatya, Tunceli and vicinities. Serum antibodies against Babesia bigemina, Babesia bovis and Babesia divergens were investigated by Indirect Fluorescence Antibody (IFA) test. In addition, peripheral blood smears were prepared and examined under a microscope. Antibodies were detected in 91 (31.9%) of 285 cattle against B. bigemina, in 4 (1.4%) against B. bovis and in 10 (3.5%) against B. divergens in Elazi? and vicinity. Antibodies were determined in 21 (7.1%) of 292 cattle against B. bigemina and 2 (0.6%) against B. divergens in Malatya and vicinity. No antibodies against B. bovis were detected in the of serum of animals collected in this area. Antibodies were determined in 12 (7.3%) of 164 cattle against B. bigemina. 1 (0.6%) against B. bovis and 2 (1.2%) against B. divergens in Tunceli and vicinity. In the microscopic examination of peripheral blood smears, Babesia sp. were observed in 4 (1.4%) and 2 (0.6%) cattle in Elazi? and Malatya, respectively. These cattle also had antibody reaction to B. bigemina., Babesia sp. were not seen in the examinations of blood smears of cattle in Tunceli province.
Elazi?, Malatya ve Tunceli İllerinde Si?irlarda Babesia Türlerinin Sero-Prevalansi
Keywords: Babesia; Cattle; IFA; Serology